Real-world evidence on non-invasive tests and associated cut-offs used to assess fibrosis in routine clinical practice - YILMAZ, YUSUF (My University, 2022)
Background & Aims: Non-invasive tests (NITs) offer a practical solution for advanced fibrosis identification in non-alcoholic fatty liver disease (NAFLD). Despite increasing implementation, their use is not standardised, which can lead to inconsistent interpretation and risk stratification. We aimed to assess the types of NITs and the corresponding cut-offs used in a range of healthcare settings. Methods: A survey was distributed to a convenience sample of liver health experts who participated in a global NAFLD consensus statement. Respondents provided information on the NITs used in their clinic with the corresponding cut-offs and those used in established care pathways in their areas. Results: There were 35 respondents from 24 countries, 89% of whom practised in tertiary level settings. A total of 14 different NITs were used, and each respondent reported using at least one (median = 3). Of the respondents, 80% reported using FIB-4 and liver stiffness by vibration-controlled transient elastography (Fibroscan®), followed by the NAFLD fibrosis score (49%). For FIB-4, 71% of respondents used a low cut-off of <1.3 (range <1.0 to <1.45) and 21% reported using age-specific cut-offs. For Fibroscan®, 21% of respondents used a single liver stiffness cut-off: 8 kPa in 50%, while the rest used 7.2 kPa, 7.8 kPa and 8.7 kPa. Among the 63% of respondents who used lower and upper liver stiffness cut-offs, there were variations in both values (<5 to <10 kPa and >7.5 to >20 kPa, respectively).
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Hepatoloji; Gastroenteroloji; Hepatology; Gastroenterology; Hepatology; NAFLD; NITs; FIB-4; Elastography; NFS